Improving Self-Control: The Influence of Role Models on Intertemporal Choices - Kedia, Gayannée; Brohmer, Hilmar; Scholten, Marc; Corcoran, Katja (Frontiers in Psychology, 2019)
The ability to delay rewards is one of the most useful qualities one may wish to develop. People who possess this quality achieve more successful careers, display better interpersonal skills and are less vulnerable to psychopathology, obesity or addictions. In the present online studies, we investigated the extent to which delay-of-reward behaviors in female participants can be improved by observing others mastering it. We developed an intertemporal choice (IC) paradigm in which participants had to make fictitious choices between sooner smaller rewards and later bigger ones (e.g. $150 in one week vs $170 in 4 weeks). In Study 1 (N = 186), we found that participants who delayed more had higher socioeconomic statuses and were less likely to procrastinate, smoke or develop obesity. In Study 2 (N = 178), we exposed female participants to a role model who, faced with intertemporal choices, chose most of the time the delayed option. Results showed that, although participants were only asked to memorize the model’s decisions, they tended to choose the delayed option more often after than before exposure to the model. In Study 3 (N = 148), we found that the direction of the influence depended on the model’s behavior: Our female participants delayed more after having seen a high delay than a low delay model. In Study 4 (N = 370), we confirmed the effect of modeling on intertemporal choices in comparison to a control condition and showed that this effect was still significant three months after exposure to the model. Altogether, these results speak in favor of a high efficacy of modeling to develop self-control in women.